Amphiphilic Compounds Assemble into Membranous Vesicles in Hydrothermal Hot Spring Water but Not in Seawater - Daniel Milshteyn; Bruce Damer; Jeff Havig; David Deamer (Life, 2018)
There is a general assumption that amphiphilic compounds, such as fatty acids, readily form membranous vesicles when dispersed in aqueous phases. However, from earlier studies, it is known that vesicle stability depends strongly on pH, temperature, chain length, ionic concentration and the presence or absence of divalent cations. To test how robust simple amphiphilic compounds are in terms of their ability to assemble into stable vesicles, we chose to study 10- and 12-carbon monocarboxylic acids and a mixture of the latter with its monoglyceride. These were dispersed in hydrothermal water samples drawn directly from hot springs in Yellowstone National Park at two pH ranges, and the results were compared with sea water under the same conditions. We found that the pure acids could form membranous vesicles in hydrothermal pool water, but that a mixture of dodecanoic acid and glycerol monododecanoate was less temperature-sensitive and assembled into relatively stable membranes at both acidic and alkaline pH ranges. Furthermore, the vesicles were able to encapsulate nucleic acids and pyranine, a fluorescent anionic dye. None of the amphiphiles that were tested formed stable vesicles in sea water because the high ionic concentrations disrupted membrane stability.